Microwave processing of Nd-Fe-Co-B magnetic materials - Tan, Xiao (2019)
Numerous studies have been performed in the field of Nd-Fe-B based permanent magnets since they possess excellent hard magnetic properties. The magnetic properties are closely related to the structure, phases present, processing route etc. High performance hard magnets can obtain their desired large energy product by interaction of magnetic moments at the nanoscale. Therefore, developing nanostructured Nd-Fe-B based magnets requires the study of novel synthesis techniques, microstructure and properties. Conventional physical techniques have limitations of inhomogeneity, contamination, poor control of microstructure and high cost due to the use of elemental rare earth metals. On the other hand, bottom-up chemical methods offer better control of structure at the nanoscale. The use of metal salts as precursors significantly reduces the cost. Hence, a cost-effective, bottom-up, microwave synthesis method is promising to produce homogenous particles by uniform microwave heating. The main objective of this project is the study of the microwave synthesis of Nd-Fe-B based magnets. The processing parameters, reaction mechanisms, characterization and property evaluation of these materials were carried out. Nanostructured Nd-Fe-B particles were prepared by microwave combustion and reduction diffusion. Microwave combustion resulted in a transformation from metal salts to mixed metal oxides consisting of CoFe2O4, NdFeO3, Nd3FeO6 and Fe2O3. Nd2(Fe,Co)14B nanoparticles were obtained by the reduction diffusion process, in which the mixed metal oxide was reduced by CaH2. The effects of processing parameters on properties and structure were studied. It was found that the structure and magnetic properties can be controlled by the microwave power. Higher microwave power resulted in larger grain size. The coercivity of the particles increased from ~ 6 kOe to ~9 kOe when the grain size increased from ~ 20 nm to ~ 60 nm. A range of reduction-diffusion annealing times was also tested. The highest energy product was obtained for reduction diffusion at 800 °C for 2 h. The CaO byproduct was removed by different chemicals. The optimum chemical was found to be NH4Cl (dissolved in methanol), which eliminated the use of water, thus avoiding the vigorous reaction between CaO and water. A novel one pot microwave processing technique was proposed and developed to synthesize Nd2Fe14B/α-Fe exchange coupled nanoparticles. Nd-Fe-Co-B mixed oxides were obtained from metal nitrates via microwave combustion followed by microwave reduction of these oxides, to form hard magnetic Nd2(Fe,Co)14B powder, in the same microwave chamber. The maximum energy product reached a value of 11.4 MGOe, it is the largest value among the reported values in chemical synthesis of Nd2Fe14B/α-Fe nanoparticles. The conventional use of a furnace for oxide reduction was eliminated. The reaction mechanisms for both microwave combustion and microwave reduction were studied for the first time. During the formation of mixed oxides, boron oxide formed first. Iron and cobalt oxides subsequently formed, followed by the formation of neodymium iron oxide. The Nd2(Fe,Co)14B alloy formed through several steps. At 350 °C, iron, cobalt and boron oxides were reduced. At 740 °C, the partial reduction of neodymium oxide to NdH5 took place. After heat treatment at 800 °C for 2 hours, the desired Nd2(Fe,Co)14B and α-Fe phases were formed. Heavy rare earths such as Dy enhance coercivity and improve thermal stability by increasing magnetocrystalline anisotropy. Hence, (Nd15-xDyx)-(Fe67Co10)-B8 (x=0, 3, 6, 9) alloys were studied. The influence of Dy substitution on the magnetic properties were investigated. (BH)max was found to be as high as 12.6 MGOe for the (Nd12Dy3)-(Fe67Co10)-B8 alloy. As Dy content increased from x=0 to x=9, coercivity increased significantly, from 8 kOe to 14.5 kOe. The thermal stability increased for higher Dy content. Analysis of the temperature dependent magnetic properties and comparison with modeling results showed that the dominant coercivity reversal mechanism was nucleation of reversed magnetic domains. This microwave synthesis technique was shown to successfully synthesize Nd-Fe-B base hard magnets. A range of parameters were studied to optimize the performance of the material. The reaction mechanism was determined. Dy could be readily alloyed to increase the thermal stability of the material.